Norwid and the Question of Philosophy - Zielichowski, Tadeusz (Sensus Historiae, 2023)
The text considers the validity of referring to Cyprian Kamil Norwid as a philosopher. By pointing to the poet’s attitude towards the concept of truth and the philosophical tradition, the author argues that Norwid was not a full-fledged philosopher and that the recognition of him as such by some Norwid scholars results from over-interpretation.